INVESTIGATION OF VACUUM-ATMOSPHERIC DRYING OF CAMEL AND MARE’S MILK - Abdizhapparova Bakhytkul Telkhozhaevna; Khanzharov Nurlan Serikbayevich; Ospanov Bakhytzhan Orazalievich; Pankina Ilona Anatol’evna; Kamalbek Dinmukhammed Kuanyshbekuly; Akhmetov Zhasurbek Mansurbekovich (Academic Scientific Journal of Chemistry, 2019)
The relevant problem of dehydration of dairy products is a subject of research in this issue. Camel and mare’s milk are of interest in this regard. Actually, for these products energy-intensive methods of vacuum and vacuum-sublimation drying are usually used, that is explained by high preservation of biochemical composition of dried materials. It causes the problem of further study and improvement of various aspects of drying processes. A method of vacuum-atmospheric drying of camel and mare’s milk is proposed, based on their dehydration in a drying plant where these processes are carried out in a parallel way. Combining processes should be based on the selection of modes of the above-mentioned drying methods. Experimental studies of vacuum-atmospheric drying of camel and mare’s milk depending on pressure and temperature of heating the medium in the vacuum chamber, as well as the speed and temperature of drying agent in the device for atmospheric drying have been conducted. Empirical equations allowing describing quite adequately processes of heat and mass transfer at vacuum-atmospheric drying of dairy products are received.